Analisis Pengaruh Unggahan Instagram @Windahtopupstore terhadap Minat Beli Followers @Windahtopupstore - Akhyar, Alghifari Fajrin Pratama; Oxcygentri, Oky (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the influence of Instagram posts by @windahtopupstore on the purchase interest of its followers, using the AIDA (Attention, Interest, Desire, Action) model. The increasing popularity of @windahtopupstore as a digital game top-up service provider highlights the need to analyze the effectiveness of its social media content in shaping consumer interest. This research employs a quantitative approach with an explanatory method. Data were collected through questionnaires distributed to followers of @windahtopupstore who were selected as research respondents. Data analysis techniques included simple linear regression and instrument validity and reliability testing. The results show that all four components of the AIDA model have a positive and significant effect on followers' purchase interest. The Attention aspect indicates that visual quality and engaging captions effectively capture audience attention. The Interest aspect shows that message clarity and positive perception increase user interest. Desire is influenced by user testimonials and emotional engagement in the content. Meanwhile, Action is driven by clear calls-to-action and the account’s responsiveness to followers inquiries.